PENANGGULANGAN TINDAK PIDANA LINGKUNGAN HIDUP - Dian Ekawaty Ismail (JURNAL LEGALITAS, 2009)
The enforcement of enviroment law according to the environment management law can be implemented both in a preventive and repressive manner. The legal instrument used is administrative law, in the formot an obligation imposed upon each person who intends to run a business, to first obtain an environmental impact assessment of the proposed business. The represive enforcement of law aims to reduce and abate exising environmental damage of pollution by using administrative law civil law and criminal law. The protection of crime can be done with dragging mutilation perpetrator and or environmental contamination to court. Sanction fallout of administration, compensatory suing and area recovery, and criminal prosecution done to mutilation perpetrator and or environmental contamination in the same case is not ne bis in idem.